“Himalayan Bridge”: A New Unstable Suspended Bridge to Investigate Rodents' Venturesome Behavior - Festucci, Fabiana; Buccheri, Clelia; Parvopassu, Anna; Oggiano, Maurizio; Bortolato, Marco; Laviola, Giovanni; Curcio, Giuseppe; Adriani, Walter (Frontiers in Behavioral Neuroscience, 2021)
While both risk-taking and avoidant behaviors are necessary for survival, their imbalanced expression can lead to impulse-control and anxiety disorders, respectively. In laboratory rodents, the conflict between risk proneness and anxiety can be studied by using their innate fear of heights. To explore this aspect in detail and investigate venturesome behavior, here we used a “Himalayan Bridge,” a rat-adapted version of the suspended wire bridge protocol originally developed for mice. The apparatus is composed of two elevated scaffolds connected by bridges of different lengths and stability at 1 m above a foam rubber-covered floor. Rats were allowed to cross the bridge to reach food, and crossings, pawslips, turnabouts, and latencies to cross were measured. Given the link between risky behavior and adolescence, we used this apparatus to investigate the different responses elicited by a homecage mate on the adolescent development of risk-taking behavior. Thus, 24 wild-type (WT) subjects were divided into three different housing groups: WT rats grown up with WT adult rats; control WT adolescent rats (grown up with WT adolescents), which showed a proclivity to risk; and WT rats grown up with an adult rat harboring a truncated mutation for their dopamine transporter (DAT). This latter group exhibited risk-averse responses reminiscent of lower venturesomeness. Our results suggest that the Himalayan Bridge may be useful to investigate risk perception and seeking; thus, it should be included in the behavioral phenotyping of rat models of psychiatric disorders and cognitive dysfunctions.